Navigating Personalised Support in Universal Credit: Local Support, Care Responsibilities, and Claimant Experiences - Shuo Fei (PLoS ONE, 2025)
This paper investigates the implementation of personalised support under Universal Credit (UC) from both administrative and claimant perspectives, based on qualitative interviews conducted across two South London case study sites. While UC is designed to promote labour market participation and simplify welfare delivery, claimants encounter multiple barriers—including digital exclusion, limited access to affordable childcare, and inconsistencies in support provision. Parents with care responsibilities face heightened pressures due to tightened work requirements and upfront childcare costs, which are often regarded as limiting their ability to comply with conditionality. Local frontline staff navigate institutional pressures from multiple governance levels within a context of resource constraints, applying discretion to tailor support to individual needs. However, this discretion may result in variable practices and uneven outcomes across different service settings. The findings underscore the tensions between the policy goal of responsibilising individuals and the complex realities of claimants’ lives.